2003
DOI: 10.1099/mic.0.26172-0
|View full text |Cite
|
Sign up to set email alerts
|

The Candida albicans CTR1 gene encodes a functional copper transporter

Abstract: Copper and iron uptake in Saccharomyces cerevisiae are linked through a high-affinity ferric/cupric-reductive uptake system. Evidence suggests that a similar system operates in Candida albicans. The authors have identified a C. albicans gene that is able to rescue a S. cerevisiae ctr1/ctr3-null mutant defective in high-affinity copper uptake. The 756 bp ORF, designated CaCTR1, encodes a 251 amino acid protein with a molecular mass of 27·8 kDa. Comparisons between the deduced amino acid seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 73 publications
6
51
0
Order By: Relevance
“…A Cactr1-null mutant displayed phenotypes that were similar to those of a S. cerevisiae mutant defective in high-affinity copper uptake. Furthermore, this mutant grew predominantly in the filamentous form and also displayed aberrant morphology in response to copper-depleted growth conditions (Marvin et al, 2003). We demonstrate here that invasive growth by C. albicans is induced by low-copper conditions and that this is augmented in a Cactr1-null strain.…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…A Cactr1-null mutant displayed phenotypes that were similar to those of a S. cerevisiae mutant defective in high-affinity copper uptake. Furthermore, this mutant grew predominantly in the filamentous form and also displayed aberrant morphology in response to copper-depleted growth conditions (Marvin et al, 2003). We demonstrate here that invasive growth by C. albicans is induced by low-copper conditions and that this is augmented in a Cactr1-null strain.…”
Section: Introductionmentioning
confidence: 65%
“…We have also shown that a double-disrupted Cactr1-null mutant grows prevalently in the filamentous form in liquid MD-BCS medium, with many cells displaying aberrant morphology (Marvin et al, 2003). These findings led us to hypothesize that copper starvation also induces invasive growth in C. albicans.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations